Tanggung Jawab Hukum Aggregator Musik Terhadap Hak Cipta Musik Pencipta Lagu - Muhammad Naufal Luthfi; Adi Sulistiyono (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to determine the position and role of music aggregators in the digital music industry and the legal liabilities of music aggregators towards the copyright of music creators. This is a normative legal research of a prescriptive nature with a statutory approach. The legal materials used are primary and secondary legal materials, through literature study, and the technical analysis of legal materials using syllogism with a deductive thinking pattern. Based on the research results and discussions, it can be seen that music aggregators have a position as partial copyright holders of music that has been entrusted to them and play a role as distributors and managers of music royalties that have been entrusted to them. Meanwhile, the legal liabilities of music aggregators as stipulated in the Copyright Law are the recording of licensing agreements, determination of royalties in accordance with prevailing industry practices and fairness, and other liabilities that arise along with licensing agreements.